Discourse Analysis of a News Text Using Cohesion and Ethnography of Speaking Theories - Angela Audreylia Sabrina; Gunawan, Salsabilla Maharani Mutiara; Pujiati, Hanip (STAIRS: English Language Education Journal, 2023)
The purpose of this study was to undertake a thorough study of a news article entitled "31 Policemen Questioned in Kanjuruhan Stadium Tragedy" by looking at both its contextual and textual elements. To analyze the data, the research used a content analysis and discourse analysis design. While the contextual study relied on Dell Hymes' ethnography of communication, notably the Speaking Model (Hymes, 1974), the textual analysis concentrated on the coherence devices given by Halliday and Hasan (1976). All essential elements, such as the setting, participants, ends, act order, key, instruments, and norms, were identified, according to the contextual analysis. The four content categories of reference, substitution, ellipsis, and conjunction were found in the textual analysis; however, the article did not fully contain all sub-categories.